Prevalence and heterogeneity of antibiotic resistance genes in Orientia tsutsugamushi and other rickettsial genomes. (January 2023) - Rao, R. Shyama Prasad; Ghate, Sudeep D.; Shastry, Rajesh P.; Kurthkoti, Krishna; Suravajhala, Prashanth; Patil, Prakash; Shetty, Praveenkumar
Abstract: Despite a million infections every year and an estimated one billion people at risk, scrub typhus is regarded as a neglected tropical disease. The causative bacterium Orientia tsutsugamushi, a member of rickettsiae, seems to be intrinsically resistant to several classes of antibiotics. The emergence of antibiotic-resistant scrub typhus is likely to become a global public health concern. Yet, it is unknown as to how common antibiotic resistance genes are in O. tsutsugamushi, and how variable these loci are among the genomes of rickettsiae. By using the comprehensive antibiotic resistance database, we explored 79 complete genomes from 24 species of rickettsiae for antibiotic resistance loci. There were 244 unique antibiotic resistance genes in rickettsiae. Both the total and unique antibiotic resistance genes in O. tsutsugamushi were significantly less compared to other members of rickettsiae. However, antibiotic resistance genes in O. tsutsugamushi genomes were more unique and highly variable. Many genes such as resistant variants of evgS, and vanS A/G were present in numerous copies. These results will have important implications in the context of antibiotic-resistant scrub typhus. Highlights: 24 species of rickettsiae were explored for antibiotic resistance genes. 244 unique antibiotic resistance genes in rickettsiae based on CARD database. Antibiotic resistance genes in Orientia tsutsugamushi were significantly less. Antibiotic resistance genes in O. tsutsugamushi were more unique and highly variable.